Sequential Acceleration Tests with Pressure Cooker Test (PCT) and UV for Backsheets of PV Modules. (September 2018) - Li, Yu-tai; Lin, Wei-you; Yang, Wei-lun; Hsieh, Cho-Fan
Abstract: The long-term reliability of backsheets for photovoltaic (PV) modules in floating systems are important due to the higher ultraviolet (UV) reflection from the water surface and the higher humidity in reservoirs or lakes. However, single tests over a long time, such as UV tests or damp heat (DH) tests for backsheets, cannot reproduce outdoor failures such as micro-cracks. Therefore, sequential acceleration tests for photovoltaic modules have been proposed, which combine DH and UV tests to reproduce multi-environment stresses. Nevertheless, DH tests usually take up to 1000–3000 h to cause degradation effects. Therefore, a pressure cooker test (PCT) is also considered as a substitute for extended DH tests since it provides test conditions with higher humidity and temperature. In this work, DH tests or PCT (121 °C /100 %Rh, 100 h), combined with UV tests, are adopted to investigate three different kinds of backsheets. The accelerated-aging test results according to different sequential test conditions are compared. The yellowing index change, peeling test, and cross-section of backsheets are also measured to evaluate the degree of degradation for different kinds of backsheets. Our results show that micro-cracks could be reproduced in sequential tests with PCT for one kind of backsheet while the other kind of backsheet did not change. This may provide an indicator to evaluate the durability of backsheets for the floating PV system application quickly.